Le langage autorisé pour penser le système éducatif - Ana Maria F. Almeida (Les éditions de la Maison des sciences de l'Homme, 2009)
This article examines the process through which education came to be seen, from the 1970's on, both as a central explanatory variable regarding Brazilian income inequality and as a public policy instrument in the economists's hands. Among other factors, this process resulted from: 1) the struggle of the professional educators to produce a national educational system, between the 1930's and the 1950's; and 2) the success of the economists in imposing their views of education as preparation of skilled labor, in the 1960's. In both periods, governments and transnational agencies facilitated an international circulation of people and ideas that was a resource manipulated by those involved in this competition.